Response to resistance training following immobilization—Influence of delaying post‐exercise meal. Issue 5 (13th October 2018) - Larsen, Mads Sørensen; Couppé, Christian; Møller, Andreas Buch; Schjerling, Peter; Andersen, Jesper Løvind; Nygaard, Rie Harboe; Langberg, Henning; Kjaer, Michael; Hansen, Mette
Abstract : Elderly women are more vulnerable to muscle disuse atrophy than men, due to lower muscle mass. Thus, identification of preventive strategies is of principal interest. We studied effects of training and timing of protein‐rich meals after exercise sessions, on skeletal muscle mass in healthy postmenopausal women. Following 2 weeks of one‐legged immobilization, a protein‐rich meal was ingested either immediately ( T 0; n = 9, 56 ± 2 years) or 2 hours ( T 2; n = 8, 57 ± 3 years) after termination of resistance exercise sessions for 6 weeks. Muscle mass, strength, and power were assessed before, after 2 weeks of lower limb immobilization and after 2 and 6 weeks of combined resistance training and diet intervention. Immobilization reduced muscle mass ( 10%), strength ( 23%), and power ( 26%), but was returned to baseline levels after 2 weeks of training. Improvements in muscle mass and strength did not differ between groups. T 0, but not T 2, increased their total daily protein intake during the training period. In conclusion, only 2 weeks of supervised resistance training counteracted reductions in muscle mass and strength in postmenopausal women after 2 weeks of immobilization. Timing of protein‐rich meals in the hours after resistance exercise did not have any impact on the effects of training.